A STUDY ON THE INFLUENCE OF ADVERTISEMENTS ON THE BUYING BEHAVIOUR OF GOLD JEWELLERY CONSUMERS' OF KOLLAM DISTRICT - Manoj M S AND Dayana Sajjanan (International Education & Research Journal, 2015)
Gold is widely distributed throughout the world, normally in very low concentration and generally in native form as metal. It has been rounding in different hands in one or other way. India's diversified customs and rituals have helped to the high demand for gold. The gold jewellery industry occupies an important position in the Indian economy. It is the fastest growing industries in the country. The study presents an overall picture about the influence of various forms of advertisements on the buying behaviour of gold jewellery consumers. The study further shows that there exists a very good potential for various forms of promotional activities on the Jewellery business in Kollam. Based on the study, the researcher had put forward certain suggestions/ recommendations. The implementation of these suggestions will go a long way in improving the brand promotion of the jewellery business in Kerala.